IMPLEMENTASI PROTOTYPE SISTEM ALARM DARURAT NIRKABEL UNTUK MENINGKATKAN KESELAMATAN WAHANA KERETA MINI PADA WISATA LOKAMERTA - Fikki, Noor Aqila Zayyana (Fakultas Teknik Universitas Diponegoro, 2025)
Safety in children's amusement rides, particularly miniature trains, is a top priority to prevent accidents and ensure visitor comfort. A common issue encountered is the slow response to potential hazards due to the lack of an effective warning system. This community service project aims to design and implement a wireless remote-based emergency alarm system capable of providing rapid alerts to operators and visitors during emergencies on the miniature train track. The system utilizes a combination of round bell and mini motor siren to produce a loud sound that can cover the surrounding area. The device is controlled via a wireless remote, enabling convenient operation without cable restrictions. The implementation method includes needs assessment, electrical circuit design, device fabrication, field testing, and user training for ride operators. The results indicate that the system can respond to activation commands in less than one second with a 100% success rate during trials. The presence of this system is expected to minimize accident risks and enhance ride safety standards. Future development could focus on integrating strobe lights and IoT technology for real-time remote monitoring.Keywords: Safety, Miniature Train Ride, Emergency Alarm, Wireless Remote, Community Service.